A Critical Analysis of the Overall Uncertainties in the Radiotherapy Treatment Process - de Almeida, Carlos Eduardo (Revista Brasileira de Física Médica, 2025)
The integration of all the steps involved in the treatment process is quite complex, as it involves the correct knowledge of the dose-response curves developed in laboratory experiments, the translation of these results to the clinic, the adequate delineation of the tumor, the appropriate dose prescribed for each type of tumor and delivered daily to the patient. For example, the correct assessment of the dose administered to a patient strongly depends on an interconnected chain of steps executed harmoniously, as the demand for accuracy of a given dosimetry procedure is very high. In this case, the measurement results must be represented the best possible reported values with their typical uncertainties to allow clinical results to be achieved and comparable with those of other institutions. The robustness of the chain of events is often fragile, with uncertainties at each stage sometimes not considered or sometimes difficult to estimate, requiring different conceptual and statistical approaches at various times in the decision-making process. As a result, as the additive sequence of uncertainties is generally not fully considered, and the clinical outcome may not be as anticipated. The objective of this review is to critically and constructively highlight the weak points observed in the interrelationship of all steps that lead to better tumor control and ultimately, to provoke a reflection on the theme.